2004
DOI: 10.1038/sj.bjp.0705670
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the subtype‐selective inhibition of cloned KATP channels by PNU‐37883A

Abstract: 1 In this study, we have used Kir6.1/Kir6.2 chimeric proteins and current recordings to investigate the molecular basis of PNU-37883A inhibition of cloned K ATP channels. 2 Rat Kir6.1, Kir6.2 and Kir6.1/Kir6.2 chimeras were co-expressed with either SUR2B or SUR1, following RNA injection into Xenopus oocytes, and fractional inhibition of K ATP currents by 10 mM PNU-37883A reported. 3 Channels containing Kir6.1/SUR2B were more sensitive to inhibition by PNU-37883A than those containing Kir6.2/SUR2B (mean fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Memantine's pharmacological properties and its mechanism of action as a moderate, non-competitive NMDA-receptor antagonist have been studied extensively. 3741 Other targets for drug development of adamantane derivatives for CNS disorders are AMPA- and K ATP channels 42,43 and the GABAergic system. 44,45 Incorporation of the adamantane moiety into neuropeptides and related signalling molecules frequently gives increased selectivities for receptor subtypes and enhanced stability in vivo , as may be exemplified by CCK derivatives equipped with an adamantane core.…”
Section: Introductionmentioning
confidence: 99%
“…Memantine's pharmacological properties and its mechanism of action as a moderate, non-competitive NMDA-receptor antagonist have been studied extensively. 3741 Other targets for drug development of adamantane derivatives for CNS disorders are AMPA- and K ATP channels 42,43 and the GABAergic system. 44,45 Incorporation of the adamantane moiety into neuropeptides and related signalling molecules frequently gives increased selectivities for receptor subtypes and enhanced stability in vivo , as may be exemplified by CCK derivatives equipped with an adamantane core.…”
Section: Introductionmentioning
confidence: 99%
“…PNU-99963 shows little selectivity between different K ATP channels, inhibiting currents in Kir6.1/SUR1, Kir6.2/ SUR2A, Kir6.2/SUR2b and Kir6.1/SUR2B with IC 50 s in the nanomolar range, and seems to act primarily through the SUR subunit [110]. PNU-37883A blocks K ATP channels of smooth muscle but not cardiac or skeletal muscle [111] and appears to interact with the pore-forming subunit, showing selectivity for Kir6.1 over Kir6.2 [112,113]. Chimaeric experiments suggest that sensitivity to PNU-37883A involves an 81 amino-acid section of the C-terminus of Kir6.1 [113].…”
Section: Pnu Compoundsmentioning
confidence: 94%
“…PNU-37883A blocks K ATP channels of smooth muscle but not cardiac or skeletal muscle [111] and appears to interact with the pore-forming subunit, showing selectivity for Kir6.1 over Kir6.2 [112,113]. Chimaeric experiments suggest that sensitivity to PNU-37883A involves an 81 amino-acid section of the C-terminus of Kir6.1 [113]. In contrast, another study has reported selectivity of PNU-37883A for SUR2B-containing channels, but little discrimination between Kir6.1/SUR2B and Kir6.2/SUR2B [110].…”
Section: Pnu Compoundsmentioning
confidence: 97%
“…Furthermore, levcromakalim (1 ìM)-induced relaxation was inhibited by U-37883A in pig urethra (K i , 0.8 ìM) with a similar potency to that found in the rat mesenteric artery (K i , 1.1 ìM; 24). Since U-37883A is generally believed to be a pharmacological tool as a specific K ir 6.1 inhibitor (11), it is tempting to speculate that the pore forming subunits of pig urethral K ATP channels are similar to those of vascular smooth muscle K ATP channels. However, the effects of U-37883A on pig urethral K ATP channels and vascular smooth muscle K ATP channels differed in several respects.…”
Section: Molecular Pharmacological Estimation Of Urethral K Atp Channmentioning
confidence: 99%
“…These results strongly suggest that U-37883A selectively binds to K ir 6.1. Recently, using K ir 6.1-K ir 6.2 chimera studies, it has been shown that the carboxy-terminus (an 81 amino acid residue section) of K ir 6.1 is an important determinant of the ability of U-37883A to inhibit channel activity even when constructs were co-expressed with SUR1 or SUR2B (11). Since structural differences between K ir 6.1 and K ir 6.2 are important in determining the sensitivity of these subunits to U-37883A, it has been suggested that U-37883A may prove useful in probing the structural and functional differences between K ir 6.1 and K ir 6.2 subtypes (11).…”
Section: Effects Of U-37883a On Recombinant K Atp Channelsmentioning
confidence: 99%